Effectiveness of early intervention on academic achievement of Hearing-Impaired children. - Azzam Khan, Muhammad (Journal of Applied Research and Multidisciplinary Studies, 2022)
It is well recognized that hearing is critical to speech and language development, communication, and learning. In fact Communication development and behavioural skills are influenced by a child’s ability to hear. Hearing is a complex process of picking up sound and attaching meaning to it. The ability to hear is critical to understanding the world around us. Children with a hearing loss often report feeling alone, without friends, and unhappy in school, particularly when their socialization with other children with a hearing loss is limited. Despite advance in technology and a greater emphasis on improving the academic performance of students with hearing impairments, these kids continue to have a more difficult time with reading, math, science and social studies.